Molecular definition of paratuberculosis pathologies by functional genomics - Smeed, Jennifer Anne (The University of Edinburgh, 2008)
Paratuberculosis (Johne's disease) is a chronic intestinal disease of ruminants caused by Mycobacterium avium subspecies paratuberculosis (MAP). Three forms have been described in sheep — multibacillary, paucibacillary and asymptomatic. Real-time RT-PCR (qPCR) and microarray analyses were used to compare gene expression in ileal tissue from sheep with the three forms of the disease in order to understand the immune responses underpinning these three defined pathologies. All animals from the infected flocks were IS900 positive by qPCR and therefore infected with MAP. Asymptomatic sheep had no clinical signs of disease, showed no evidence of acid-fast bacteria (ZN-), exhibited normal histology of the terminal ileum and were seronegative. Paucibacillary sheep were ZN- and showed lymphocyte/eosinophil infiltrate into the lamina propria. 2/6 of the paucibacillary animals were seropositive. Multibacillary sheep had high numbers of ZN+ bacteria associated with infiltrating sheets of epithelioid macrophages and were seropositive. Control sheep were IS900 negative and thus uninfected with MAP.

qPCR experiments compared the expression of the following genes - IL-la, IL-1B, IL-3, IL-6, IL-8, IL-10, IL-12p40, IL-18, CD34, CXCR4, GM-CSF, IFNy, IGFBP-2, IGFBP-6, TGF6, TIRAP, TNFa, TRAF-land TRAM. The results confirmed that pauci- and multibacillary forms are linked to the differential expression of IFNy and IL-10 respectively, but imply that polarisation is incomplete, with upregulation of both proinflammatory IL-18 and anti-inflammatory TGFB in both disease forms. Increased levels of the proinflammatory cytokines IL-ip, IL-8, TNFa and TRAF-1, indicative of persistent inflammatory lesions, were observed in clinical tissues. IL-3 was detected at low levels in all infected animals but never in uninfected control samples. IGFBP-6 was upregulated and CXCR4 down-regulated in paucibacillary samples compared to multibacillary samples. SNP analysis was carried out on these genes, identifying three novel SNPs in each gene, but none were linked to disease pathology.

Microarray experiments discovered 63 differentially expressed genes. Four genes were found to be differentially expressed in infected tissue compared to uninfected controls, and a further eight in clinical tissues compared to uninfected controls. Eight genes were differentially expressed in clinical tissue compared to asymptomatic tissue. Seven genes were quantified by qPCR and validated the microarray data well. Pathway analysis of the microarray data identified several immune pathways that are involved in pathogenesis. Infected tissues displayed up-regulation of the genes involved in complement activation, and downregulation of TCR signalling and MHC class II genes. In addition, clinical tissues displayed up-regulation of genes involved in the JAKSTAT and TLR2 signalling pathways, NK cell cytotoxicity and antibody production. Multibacillary tissues also displayed up-regulation of genes involved in leukocyte migration.

Overall, these data confirm that multibacillary pathology is linked to type 2 and paucibacillary pathology is linked to type 1 immune responses, and identify novel genes and gene pathways for future analyses.